Outcomes following coronary artery bypass grafting and percutaneous transluminal coronary angioplasty in the stent era: a prospective study of all 9890 consecutive patients operated on in Scotland over a two year period. Issue 6 (1st June 2001) - Pell, J P; Walsh, D; Norrie, J; Berg, G; Colquhoun, A D; Davidson, K; Eteiba, H; Faichney, A; Flapan, A; Hogg, K J; Jeffrey, R R; Jennings, K; et al.
Abstract : OBJECTIVE: To determine current outcomes of percutaneous transluminal coronary angioplasty (PTCA) and coronary artery bypass grafting (CABG). DESIGN: The Scottish coronary revascularisation register provided prospectively collected data on case mix and in-hospital complications for all revascularisation procedures between April 1997 and March 1999 (4775 PTCA; 5115 CABG). Linkage to routine hospital discharge and death data provided follow up information on survival and repeat revascularisation. RESULTS: Stents were used in 51% of PTCA procedures. CABG patients were older, had more severe coronary disease, and had greater comorbidity. PTCA was more likely to be undertaken as an urgent or emergency procedure. Perioperative death and urgent surgery followed 0.3% and 0.6% of PTCA procedures, respectively. Case fatality rates were higher following CABG, with 6.7% dead within two years compared with 3.4% following PTCA. PTCA was more often followed by readmission for ischaemic heart disease, repeat angiography, or revascularisation: 22.8% of patients had repeat revascularisation within two years, compared with 1.8% following CABG. CONCLUSIONS: The severity of coronary heart disease was greater than in previously published registry studies and randomised trials. Despite this, overall survival figures were comparable and repeat revascularisation rates lower, particularly following PTCA. Perioperative death and urgent surgery following PTCA were also lower. These favourable outcomes may be attributable, in part, to increased use of bail out and elective stenting.